The Factors Influence Corporate Social Responsibility (CSR) Disclosure in Indonesian State-Owned Enterprises (SOEs) - Elvina, Elvina (Undergraduate Program in Accounting, Department of Accounting, Faculty of Economics and Business, Universitas Tanjungpura, 2024)
This research is motivated by the fact that companies claim to have implemented CSR but are still involved in cases related to social and environmental issues. The purpose of this study was to examine the influence of company size, company age, sector type, profitability as measured by ROA, green accounting, board of directors’ size, and the involvement of female board members on CSR disclosure. The method used was a quantitative method with multiple linear regression analysis. The testing process was carried out using SPSS version 27 as the analysis tool on a sample of 50 Indonesian SOEs listed on the IDX, using data from 2018–2022. The results of this study indicate that green accounting has a positive influence on CSR disclosure; company size and profitability, as measured by ROA, have a negative influence on CSR disclosure; while company age, sector type, board of directors’ size, and the involvement of female board members do not influence CSR disclosure. Thus, H1, H2, H3, H4, H6, and H7 are rejected, while H5 is accepted.